2021
DOI: 10.1177/10711007211055460
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Bone Morphology in Charcot-Marie-Tooth Disease

Abstract: Background: Although long suspected, it has yet to be shown whether the foot and ankle deformities of Charcot-Marie-Tooth disease (CMT) are generally associated with abnormalities in osseous shape. Computed tomography (CT) was used to quantify morphologic differences of the calcaneus, talus, and navicular in CMT compared with healthy controls. Methods: Weightbearing CT scans of 21 patients (27 feet) with CMT were compared to those of 20 healthy controls. Calcaneal measurements included radius of curvature, sag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Michalski et al have recently demonstrated, using 3D techniques, that there is a change in the bony morphology of these bones. 26 Their study was done using the same software as this study and therefore it is likely that the automated analysis was able to account for these differences where manual measurement may not.…”
Section: Discussionmentioning
confidence: 99%
“…Michalski et al have recently demonstrated, using 3D techniques, that there is a change in the bony morphology of these bones. 26 Their study was done using the same software as this study and therefore it is likely that the automated analysis was able to account for these differences where manual measurement may not.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this difference arose from abnormal osteology or joint malalignment, from single or multiple segments of the foot, remained unclear. In a recent study, Michalski et al 12 demonstrated that CMT patients often have aberrant osseous morphology of the calcaneus and talus, in particular, demonstrating a more curved calcaneal body, horizontal posterior facet orientation, and reduced talar neck declination. Although these abnormalities contribute to notable differences between CMT and normal individuals, they are not sufficient to explain the severity of global deformity in cavovarus foot.…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective cohort study approved by the Institutional Review Board. Patient selection and weightbearing computed tomography (WBCT) protocol were identical to the methodology in the corollary part of the study by Michalski et al 12 In summary, 27 scans in 21 patients met criteria for the study cohort; including 6 patients who had bilateral WBCTs. This group included 10 females and 11 males, with an average age of 27.5 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiological evaluation of cavus foot should also include the Coleman block test in order to assess the flexibility of the foot. In the recent literature, Dr. Michalski [36] and Dr. Tonya An [37] have conducted high quality research about bone morphology changes in cavus foot. Their research results indicate that the TN coverage angle (Figure 7) plays an important role in evaluating the effect of cavus foot correction.…”
Section: Radiological Evaluationmentioning
confidence: 99%